Development of a movable 4πβ(LS)−γ coincidence counting system for activity standardization of β−γ emitters. (August 2021) - Lee, J.M.; Agung, A.; Hwang, S.H.; Lee, K.B.; Hwang, H.Y.
Abstract: A new movable 3PM-γ coincidence system, based on 4πβ(LS)−γ coincidence counting, for activity measurement of β-γ emitters has been designed at the Korea Research Institute of Standards and Science (KRISS). The system incorporates 3 PM tubes on the plane and two detectors placed above and below the center of the plane. The 3 PM tubes for β–counters in the plane are movable up to 100 mm from a liquid scintillation vial, thus enabling the variation of β−detection efficiencies by a geometrical technique. A NaI(Tl) γ-counter was set above for the present work. The β-event is determined by counting the logical sum of three double coincidences. All the necessary electronics, i.e., logical sum, adjusting the duration of dead-time of each counting channel and coincidence resolving times, and analyzing coincidence relation, were specially designed to be fabricated in an integrated circuit. Details of the detectors, the electronics, the overall movable 3PM-γ coincidence system are presented, as well as the results of investigations to assess its operating characteristics. Validation measurements have been performed with 60 Co and 57 Co sources. The highest β−detection efficiency achieved with 60 Co and 57 Co was 97% and 95%, respectively. The activity concentration determined with a new system agreed with calibrated values within the uncertainty range. Further results from validation measurements and the corresponding uncertainty budgets are presented. Highlights: Design of movable 3PM-γ coincidence counter based on 4πβ (LS) −γ (NaI(Tl)) system. Logical sum of three double coincidences for β event. Validation of geometrical efficiency variation & linear efficiency-extrapolation. Apply on activity measurement of 60 Co and 57 Co.